Molecular detection of Staphylococcus pseudintermedius in canine pyoderma - Alvarez V., Luis (2020)
Pyoderma is one of the most diagnosed skin diseases in canines. Among the agents most involved were Staphylococcus intermedius; however, in 2005 it was reclassified into three phenotypically similar species: S. intermedius, S. pseudintermedius and S. delphini, which cannot be identified by conventional biochemistry. Various studies report S. pseudintermedius as the most frequently isolated bacterial agent in pyoderma. Therefore, this study evaluated the presence of S. pseudintermedius using PCR-RFLP in 141 Staphylococcus sp isolates in the Laboratory of Bacteriology of the Faculty of Veterinary Medicine, Universidad Nacional Mayor de San Marcos, Lima, Perú from cases of canine pyoderma in the period 2016-2018, finding that 87.9% of Staphylococcus sp isolates have been identified as S. pseudintermedius and 12.1% as Staphylococcus sp.